Whole exome sequencing of human papillomavirus-related multiphenotypic sinonasal carcinoma: a case report - Cubides-Córdoba, María Camila; Sánchez-Fernández, Paula; Mendoza-Pacas, Guillermo E.; Cabal, Virginia N.; García-Marín, Rocío; Lorenzo-Guerra, Sara Lucila; García-Velasco, Fabián; Hermsen, Mario A.; Llorente, José Luis (Frontiers in Oncology, 2024)
Human Papillomavirus (HPV) related Multiphenotypic Sinonasal Carcinoma (HMSC) is a rare tumor with features of both atypical squamous cell and adenoid cystic carcinoma, making diagnosis challenging. Approximately 80% of HMSC cases carries HPV type 33 followed by type 35. We present a patient with HMSC.Pathological classification was aided by immunohistochemistry (IHC). The presence of HPV-DNA was tested using PCR and HPV E6/E7 expression by RNA in situ hybridization (RNA ISH). Whole exome sequencing (WES) was used to identify somatic gene mutations and copy number alterations.A 55-year-old male presented with an HMSC in the right nostril. Histological examination showed a solid basaloid subtype with mucinous spaces and ductal structures. IHC showed positive staining for SOX-10, SMA, p40, p63, PanCK, CK8 and MYB. Diffuse positive staining for p16 was observed and PCR and RNA ISH indicated the presence of HPV type 35. The patient was treated with endoscopic surgery and radiotherapy and is currently alive and recurrence-free after 16 months of follow-up.WES revealed 38 somatic sequence variants and several chromosomal regions with copy number alterations, including a copy number gain at 6q23 where MYB is located. EP300, ZNF22, ZNF609 and LRIG3 are some of the genes whose mutations were indicated as probably pathogenic. We did not find mutations predictive for drug response according to the ESMO Scale for Clinical Actionability of Molecular Targets database. This is the first report of WES analysis of an HMSC, in this case associated with HPV type 35. The detected mutation in EP300 and the overexpression of MYB may serve as molecular targets for personalized therapy.